A Comparative Study on Temporary Shelters for Emergency Disasters of Thailand: Case Study of Emergency Shelter of Japan - Doungjai Limsaksri; Yanin Rugwongwan (Journal of Namibian Studies History Politics Culture, 2023)
Since there were some spatial physical problems of temporary shelters in Thailand regarding the use of temples as temporary shelters for supporting victims of emergency disasters that failed to meet with international standards, the researcher conducted this study to decrypt spatial physical condition of temporary shelter of Japan that was the case study of this research. The objective of this research was to conduct comparative study on temporary shelters for emergency disasters of Thailand: case study of emergency shelter of Japan. Research process used in this research was qualitative research and research tools were divided into 2 parts including: document research for studying on documents related to temporary shelters of Japan and Thailand; and field survey. The samples were obtained from considering on 5 temples. The results Japan’s temporary shelter that was the case study of this research the residential place of victims was a gymnasium located in primary school with utility spaces for supporting behaviors and daily life activities of victims. When comparing to Thailand, the building used as temporary shelter of victims was multipurpose building the major utility space of multipurpose building was the hall. Conclusions on environmental improvement or arrangement of temples for supporting temporary shelters to meet with international standards were divided into 3 alternatives. The researcher divided suggestions in to 2 dimensions including: 1) Operations of Government Sector; and 2) Participation in Establishment of Temporary Shelters in Temple Areas, in Thai context in order to obtain temporary shelters with international standards.
Keywords: Urban and spatial planning